Polymer-carbon nanotube composites preparation, properties and applications - McNally, Tony; Pötschke, Petra (Woodhead Pub., 2011)
Understanding the properties of polymer carbon nanotube (CNT) composites is the key to these materials finding new applications in a wide range of industries, including but not limited to electronics, aerospace and biomedical/bioengineering. Polymer-carbon nanotube composites provides comprehensive and in-depth coverage of the preparation, characterisation, properties and applications of these technologically interesting new materials. Part one covers the preparation and processing of composites of thermoplastics with CNTs, with chapters covering in-situ polymerization, melt processing and CNT surface treatment, as well as elastomer and thermoset CNT composites. Part two concentrates on properties and characterization, including chapters on the quantification of CNT dispersion using microscopy techniques, and on topics as diverse as thermal degradation of polymer/CNT composites, the use of rheology, Raman spectroscopy and multi-scale modelling to study polymer/CNT composites, and CNT toxicity. In part three, the applications of polymer/CNT composites are reviewed, with chapters on specific applications such as in fibres and cables, bioengineering applications and conductive polymer CNT composites for sensing. With its distinguished editors and international team of contributors, Polymer-carbon nanotube composites is an essential reference for scientists, engineers and designers in high-tech industry and academia with an interest in polymer nanotechnology and nanocomposites. Provides comprehensive and in-depth coverage of the preparation, characterisation and properties of these technologically interesting new materialsReviews the preparation and processing of composites of thermoplastics with CNTs, covering in-situ polymerization, melt processing and CNT surface treatmentExplores applications of polymer/CNT composites such as in fibres and cables, bioengineering applications and conductive polymer CNT composites for sensing.
Keywords: Nanotubes.; Nanocomposites (Materials); Polymeric composites.; Carbon composites.; elektronické knihy; electronic books